ANALYZING THE DEIXIS OF SONG LYRICS IN ADELE ENTITLED ALL I ASK - Rian Abdus Salamudin; Efransyah Efransyah (IKIP Siliwangi, 2021)
The title of this research is analyzing the Deixis of Song Lyrics in Adele entitled “All I Ask”. The researchers used a descriptive qualitative method in this research. This research are aimed to find out the types of deixis (Personal, Spatial, and Temporal) and the most dominant deixis which found in the lyrics of Adele's song. Based on the results and discussion, the researchers concluded that all deixis which proposed by Yule are found in Adele’s song lyrics. Personal deixis is mostly found in 38 occurrences dominate in this song. The words are “I, me, we, our, ours, us, and my” as the first person deixis, “you, and your” as the second person deixis, and “they and it” as the third person deixis. In the second position is spatial deixis, this, and in your eyes which found in 5 occurrences. The third position is temporal deixis, coming next, tomorrow, and last night which found in 3 occurrences. Keywords: Deixis, Song, Lyric